Computational simulation of biaxial fatigue behaviour of lotus-type porous material - J. Kramberger; M. Šori; M. Šraml; S. Glodež (Fracture and Structural Integrity)
A computational simulation of low-cycle fatigue behaviour of lotus-type porous material, subjected to biaxial in-phase loading cycles is presented in this paper. Fatigue properties of porous materials are less frequently published in the literature. This paper evaluates computational analyses, where different pore distribution and biaxial loading conditions in relation to the pore orientations is considered in each simulation. The fatigue analysis is performed by using a damage initiation and evolution law based on the inelastic strain energy. The computational results are subjected to the appropriate statistical analysis, because of different pore topology a different fatigue lives are obtained on the same loading level. Results of computational simulations show also a qualitative understanding of porosity influence on low-cycle fatigue failures of lotus-type porous material under biaxial loading conditions.